Imperialism and the Rhetoric of the Threat: Islamic Fundamentalism in Western Scholarship - Ali Munhanif (Refleksi, 2000)
The way in which Western scholars understand the nature of religion and the relationship of religion to politics and society greatly determine their expectations and judgements.